2009
DOI: 10.1007/s12149-009-0276-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct radionuclide cystography imaging in colovesical fistula due to inguinal hernia operation complication

Abstract: Colovesical fistula is an abnormal connection between the enteric and urinary systems, usually sigmoid colon, caused by various conditions. One cause of colovesical fistula is iatrogenic injury, such as induced by inguinal hernia surgery. We present a case of colovesical fistula. A 57-year-old male was admitted to a local hospital with complaints of dysuria and pneumaturia. He had a past history of total extraperitoneal laparoscopic inguinal hernia repair operation 7 years previously for bilateral inguinal her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Iatrogenic fistulae are induced by surgical procedures, including augmentation cystoplasty [26], prostatectomy, rectal resections and laparoscopic inguinal hernia repair [3,27], or endoscopic procedures as colorectal stenting for malignant obstruction [28]. Iatrogenic EVF can represent a rare complication of indwelling urethral catheterisation, generally in patients with previous pelvic radiotherapy [29].…”
Section: Aetiologymentioning
confidence: 99%
“…Iatrogenic fistulae are induced by surgical procedures, including augmentation cystoplasty [26], prostatectomy, rectal resections and laparoscopic inguinal hernia repair [3,27], or endoscopic procedures as colorectal stenting for malignant obstruction [28]. Iatrogenic EVF can represent a rare complication of indwelling urethral catheterisation, generally in patients with previous pelvic radiotherapy [29].…”
Section: Aetiologymentioning
confidence: 99%
“…There was a report in which direct radioisotope cystography detected colovesical fistula and provided further information on fistula [5]. In another report, Tc-99m sulfur colloid SPECT/CT found peritoneal fistula successfully after kidney transplantation [12].…”
Section: Discussionmentioning
confidence: 98%
“…Tamam et al [5] reported cystography imaging in colovesical fistula with Tc-99m DTPA and provided dynamic subsequent images. We also chose Tc99m DTPA, as it is a water-soluble, non-irritatant, and particularly, easily absorbed radiopharmaceutical in case of unexpected leakage through the fistula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iatrogene Fisteln werden durch chirurgische Eingriffe verursacht, z. B. nach Augmentationszystoplastik [26], Prostatektomie, rektalen Resektionen sowie laparoskopischen inguinalen Herniotomien [3,27] oder endoskopischen Eingriffen wie kolorektalen Stentimplantationen wegen maligner Obstruktion [28]. Die iatrogene EVF kann eine seltene Komplikation von urethralen Dauerkathetern sein, im Allgemeinen bei Patienten mit früherer Strahlenbehandlung des Beckens [29].…”
Section: > Evf Ist Eine Komplikation Entzündlicher Oder Neoplastischeunclassified